2015
DOI: 10.18034/ajtp.v2i2.385
|View full text |Cite
|
Sign up to set email alerts
|

XBRL Acceptance in India: A Behavioral Study

Abstract: XBRL is fast becoming the new paradigm for reporting of financial information digitally. XBRL brings structure to business information with comprehensive description and contextual information for advanced analysis. It enhances the efficiency of financial reporting, accuracy, timeliness and reliability of financial data. Many Indian companies still resist using it. The present research uses technology acceptance model to analyze the perception of financial experts in respect of acceptance of XBRL as reporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…There is a significant positive influence between perceived ease of use (PEOU) and the intention to use (ITU) MBRS in Malaysia. Chouhan and Goswami (2015) found that perceived ease of use and perceived usefulness had a positive impact on attitudes towards using XBRL, supported by Uyob et al (2019aUyob et al ( , 2019b (study before the implementation of MBRS). However, the results could be different after MBRS implementation.…”
Section: Perceived Usefulnessmentioning
confidence: 83%
See 1 more Smart Citation
“…There is a significant positive influence between perceived ease of use (PEOU) and the intention to use (ITU) MBRS in Malaysia. Chouhan and Goswami (2015) found that perceived ease of use and perceived usefulness had a positive impact on attitudes towards using XBRL, supported by Uyob et al (2019aUyob et al ( , 2019b (study before the implementation of MBRS). However, the results could be different after MBRS implementation.…”
Section: Perceived Usefulnessmentioning
confidence: 83%
“…Park and Lee (2013) found that attitude towards XBRL was significantly related to the intention to use XBRL among small and medium-sized enterprises. However, Chouhan and Goswami (2015) indicated that there was no effect of practitioners' attitudes on their intention to use XBRL in North India. Nevertheless, Ilias et al (2020a), predicting MBRS usage behaviour, state that attitude is one of the important factors.…”
Section: Attitudementioning
confidence: 94%
“…Chouhan and Goswami (2015): According to current studies, perceived utility and perceived ease of use have a huge impact on attitudes toward using technology. The results of the study also point to some broad explanations for XBRL's slow adoption in India.…”
Section: Revision Of Xbrl Mandatesmentioning
confidence: 99%
“…Abu-assi et al (2014) Perceived usefulness Perception of preparers who believed that using the XBRL submission system will improve their job performance. Chouhan & Goswami (2015).…”
Section: Perceived Compatibilitymentioning
confidence: 99%